(3eONd cejs - (3MdGd GHQGgje(B, (3GdYHOs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2002)
(3GdGfJGL hGdGfJGLjI,GdJfHD HGdWdH,CSGdjH LOhdI GdGfJGL aj GdGLd GdbUjQ,GdJNWjW GdGLeGdj,GdHQeLI GdNWjI,GdMd GdHjGfj,GdJNWjW h eJGHYI GdeTQhYGJ,feGPL GdeMGcGI,fXQjI Uaha GdGfTWGQs
(3GdeQGLY U(B.327s
Keywords: (3GdEfJGLs; (3GdGfJGLjIs; (3GdWdHs